Numerical simulation and experimental study on flexible buoyancy material of hollow glass microsphere and silicone rubber for small deep-sea soft robots. (December 2020) - Hou, Jiaoyi; Shi, Yuntai; Li, Zihao; Wu, Jiaqi; Gong, Yongjun; Zou, Weifeng; Zuo, Han; Ning, Dayong
Highlights: The content of impurity phase in the material was studied by Digital Image Processing method. The variation of hardness of materials was studied by micro-unit method. By using numerical calculation method, the prediction formula of elastic modulus suitable for the flexible buoyancy material in this paper is obtained. The water absorption of FBMs is calculated by simulating the deep sea environment with a deep sea simulator, and the bubble volume shrinkage ratio is introduced to analyze the performance of FBMs. Abstract: As a novel type of robot, soft robots are used in various subtle scenes. Buoyancy materials used in small deep-sea soft robots need to have characteristics of low density and certain flexibility. Thus, in order to adapt the flexible buoyancy material (FBM) underwater equipment to the complex deep sea environment, hollow glass microspheres (HGMs) are used as fillers and silicone rubber (SR) as matrix to prepare FBM. The main properties, such as density, tensile strength, elastic modulus, hardness and water absorption are tested and analyzed to make the preparation of FBMs serialized. Scanning electron microscope (SEM) is used for morphological observations, which can distinguish the bubbles and broken HGMs in FBMs. Moreover, digital image processing (DIP) method is used to determine the content of the impurity phase in the material. Then, the influences of the impurity phase on the properties of the material are also studied. In addition, the reason of hardness change is analyzed by micro element simulation method. Results show that the performance of FBMs is relatively balanced when the mass fraction of HGM is 20%. FBMs can be used as structural material or buoyancy material of small underwater soft robots for tests and applications. Graphical abstract: Image, graphical abstract